BIOLOGY AND BENEFICIAL PROPERTIES OF ARTICHOKE (CYNARA SCOLYMUS L.) (Modern American Journal of Biological and Environmental Sciences, 2025)
The article is devoted to the distribution, morphology, biological characteristics, growth and development stages, ecological requirements, and agrotechnical aspects of the artichoke plant. Artichoke is a vegetable plant that contains biologically active substances beneficial to human health and, like many vegetables, is easily digestible and has a dietary character. It is considered one of the important crops in agriculture.